Strategi Pengembangan Promosi Secara Digital Pada Usaha Bagoyam Lidia di Pasar Paramount Gading Serpong - Rimadias, Santi; Ongdy, Angelica; Isabel, Angeliqe; Lie, Apricia Jocelyn; Setiawan, Keila Marie; Sanjaya, Lili; Chen, Liviaxander (Abdimas Indonesian Journal, 2023)
The use of social media in digital marketing is an essential approach today. Approach and marketing through social media is a form of approach that can increase business excellence in MSMEs. By taking an effective social media approach, MSMEs also have the potential to achieve very broad market targets and marketing. Not only marketing, a unique and modern logo design is also needed to attract more customers. Based on what the service team analyzed, MSME Bagoyam Lidia has several shortcomings such as a lack of promotion on social media and not having a clearer business identity such as a logo. With this, the service team has made improvements, especially in these areas, in order to fulfill the goal of the service team to increase Bagoyam Lidia's brand awareness and continuous promotion on social media. The community service team provides assistance in creating and monitoring social media for marketing at Bagoyam Lidia MSMEs, Pasar Paramount Tangerang, namely on Instagram and Tiktok so as to attract potential consumers to come and buy. After completing the community service process for MSMEs, the service team has succeeded in creating a logo and changing the design of the Bagoyam Lidia stand so that it can attract more consumer attention. The service team also succeeded in creating social media accounts and content which received quite a good response from the public.